Pertussis toxin has eukaryotic-like carbohydrate recognition domains. - Saukkonen, K (1992)
Bordetella pertussis is bound to glycoconjugates on human cilia and macrophages by multiple adhesins, including pertussis toxin. The cellular recognition properties of the B oligomer of pertussis toxin were characterized and the location and structural requirements of the recognition domains were identified by site-directed mutagenesis of recombinant pertussis toxin subunits. Differential recognition of cilia and macrophages, respectively, was localized to subunits S2 and S3 of the B oligomer. Despite greater than 80% sequence homology between these subunits, ciliary lactosylceramide exclusively recognized S2 and leukocytic gangliosides bound only S3. Substitution at residue 44, 45, 50, or 51 in S2 resulted in a shift of carbohydrate recognition from lactosylceramide to gangliosides. Mutational exchange of amino acid residues 37-52 between S2 and S3 interchanged their carbohydrate and target cell specificity. Comparison of these carbohydrate recognition sequences to those of plant and animal lectins revealed that regions essential for function of the prokaryotic lectins were strongly related to a subset of eukaryotic carbohydrate recognition domains of the C type.